Eksplorasi Konsumsi Brand Join Kopi - Samuel Dwi Kurnia; Anthony Edward Sugiman (Universitas Prasetiya Mulya, 2021)
Coffee consumption in Indonesia has seen significant improvement over the last 5 years, specifically – coffee shops and café. News showed that there are substantial increase in production and domestic consumption within the coffee industry. Coffee consumption are often related to the “nongkrong” culture which many Indonesian youths adopt. The term nongkrong is defined as a form of social activity in which at least 2 people are involved without any other purpose besides enjoying each others’ company. Regarding the activities carried out while consuming coffee, little is known about what consumption actually occurs. Facing a growing industry, it is necessary to have an in-depth understanding of consumer behavior and consumption that occurs in order to capitalize on these development opportunities. The purpose of this study is to explore coffee consumption through Holt’s typology (1995). The object of this research is JOIN Kopi, a modest coffee shop located within the Bulungan area, South Jakarta. The data collected are of qualitative nature, thus the use of in-depth interviews are in accord with exploring meaning and consumption. This study will be divided into 4 major themes; experience, integration, play, and classification, with various adjustments around the coffee industry, specifically coffee shop consumption. The study found expansions of meaning surrounding accounting and appreciating practices; the use of self-competence in assimilating practices, redefining producing practices; the addition of bonding practices along with expansions within the play metaphor, specifically socializing.